2019
DOI: 10.1002/ece3.5868
|View full text |Cite
|
Sign up to set email alerts
|

Generalized host‐plant feeding can hide sterol‐specialized foraging behaviors in bee–plant interactions

Abstract: Host-plant selection is a key factor driving the ecology and evolution of insects.While the majority of phytophagous insects is highly host specific, generalist behavior is quite widespread among bees and presumably involves physiological adaptations that remain largely unexplored. However, floral visitation patterns suggest that generalist bees do not forage randomly on all available resources. While resource availability and accessibility as well as nectar composition have been widely explored, pollen chemis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
29
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(35 citation statements)
references
References 64 publications
6
29
0
Order By: Relevance
“…For example, Standifer et al (1968) suggested a lack of phylogenetic constraints of pollen sterol composition based on the evidence of large variation in three Salicaceae species. Vanderplanck et al (2020a), in contrast, found similar pollen sterol composition within the genus Salix and our interpretation of the data published by Villette et al (2015) suggested the occurrence of some pollen sterols was phylogenetically constrained. Since most studies focused on a few plant species, they were insufficient to reach a general overview of the patterns of pollen sterol diversity across plant taxa and their drivers.…”
Section: Introductionsupporting
confidence: 65%
See 3 more Smart Citations
“…For example, Standifer et al (1968) suggested a lack of phylogenetic constraints of pollen sterol composition based on the evidence of large variation in three Salicaceae species. Vanderplanck et al (2020a), in contrast, found similar pollen sterol composition within the genus Salix and our interpretation of the data published by Villette et al (2015) suggested the occurrence of some pollen sterols was phylogenetically constrained. Since most studies focused on a few plant species, they were insufficient to reach a general overview of the patterns of pollen sterol diversity across plant taxa and their drivers.…”
Section: Introductionsupporting
confidence: 65%
“…This suggests an overall trade-off of these two groups, the balance of which may be governed by DWF1 (sterol-Δ 24 -reductase) activity. Data from previous studies (Villette et al, 2015;Vanderplanck et al, 2020a) The composition of phytosterols appears to be tissue-dependent (Nes, 1990;Nes et al, 1993). For example, 24-methylenecholesterol has been identified as the main pollen sterol in many Cactaceae (Fig.…”
Section: Phylogenetic Structure Of Pollen Sterolsmentioning
confidence: 95%
See 2 more Smart Citations
“…Higher pollen sterol levels have been repeatedly linked to bumble bee colony health and fitness [24,25]. Dietary needs based on the composition of lipid and sterol nutrients are likely to be species-specific; different bee taxa show characteristic body-lipid composition likely derived from their pollen diet [46], and lipid preference may guide host-plant choice for specialists and generalists alike [47]. The overconsumption of diets too high in lipid content can be detrimental to bumble bee health and possibly lead to their avoidance [8,43].…”
Section: Introductionmentioning
confidence: 99%